Association between self-reported oral health, tooth loss and atherosclerotic burden - Maximiliano Schünke Gomes; Patrícia Chagas; Dalva Maria Pereira Padilha; Paulo Caramori; Fernando Neves Hugo; Carla Helena Augustin Schwanke; Juliana Balbinot Hilgert (Sociedade Brasileira de Pesquisa Odontológica, 2012)
Previous studies have suggested that oral diseases may influence the development of atherosclerosis. The aim of this study was to test the hypothesis that poor self-reported oral health (SROH) and tooth loss are positively associated with coronary atherosclerotic burden (CAB). 382 consecutive subjects undergoing coronary angiography were included. Socio-demographic characteristics, cardiovascular risk factors and oral health status were collected using a standardized questionnaire, including data on SROH and use of dental prosthesis. Number of teeth and anthropometric measures were collected through clinical examinations. CAB at coronary angiography was quantified using the Friesinger score (FS). Prevalence ratios (PR) were calculated with Poisson regression analyses. Mean age was 60.3 ± 10.8 years, with 63.2% males. In the bivariate analysis, there was a significant association (p < 0.05) between CAB and age (> 60y) (PR = 1.01, 95%CI = 1.02-1.16), male gender (PR = 1.11, 95%CI = 1.03-1.19), smoking (PR = 1.08, 95%CI = 1.01- 1.16), hypertension (PR = 1.12, 95%CI = 1.03-1.22), diabetes (PR = 1.17, 95%CI = 1.05-1.21), poor SROH (PR = 1.22, 95%CI = 1.02-1.46) and tooth loss (< 20teeth present) (PR = 1.10, 95%CI = 1.02-1.19). The use of dental prosthesis was not associated with CAB. The multivariate models, adjusted for age, gender, smoking, hypertension, diabetes and dyslipidemia showed that poor SROH (p = 0.03) and tooth loss (p = 0.02) were independently associated with CAB, confirming the study hypothesis.